2020
DOI: 10.30886/estima.v18.917_in
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-epidemiological profile of patients with pressure injuries in the hospital context

Abstract: Objective: describe the clinical-epidemiological profile of patients with pressure injuries admitted to a university hospital. Method: descriptive study with 122 patients with pressure injuries admitted to a university hospital between January 2018 and December 2019. Data were collected from patients’ medical records and from the Serviço Assistencial de Cuidados com a Pele (Skin Care Assistance Service) database. Descriptive statistics were used for data analysis. Results: pressure injuries predominated among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the study conducted in Bauru 5 , there was a greater proportion of obese patients than in the current study: 43.90% (against 33.82%), and there was no case of low BMI (whereas 4.41% of patients in this study were underweight). Studies evaluating specifically patients with pressure injuries [21][22][23]27 found a higher proportion of patients with nutritional status deficiencies: 56.6% of 122 patients in the city of Aracaju, in the Brazilian state of Sergipe, were either underweight or obese 21 ; and an analysis of 324 institutionalized elderly in the city of João Pessoa, in the Brazilian state of Paraíba, found that patients with a nutritional status impairment had a 3.021 odds ratio of presenting a pressure injury 22 . A multicentric study 23 assessing 473 patients in seven different Brazilian state capitals found malnutrition to be one of the main risk factors for the development of pressure injuries (odds ratio of 10.46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted in Bauru 5 , there was a greater proportion of obese patients than in the current study: 43.90% (against 33.82%), and there was no case of low BMI (whereas 4.41% of patients in this study were underweight). Studies evaluating specifically patients with pressure injuries [21][22][23]27 found a higher proportion of patients with nutritional status deficiencies: 56.6% of 122 patients in the city of Aracaju, in the Brazilian state of Sergipe, were either underweight or obese 21 ; and an analysis of 324 institutionalized elderly in the city of João Pessoa, in the Brazilian state of Paraíba, found that patients with a nutritional status impairment had a 3.021 odds ratio of presenting a pressure injury 22 . A multicentric study 23 assessing 473 patients in seven different Brazilian state capitals found malnutrition to be one of the main risk factors for the development of pressure injuries (odds ratio of 10.46).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, smoking and/or alcoholism were present in 19.8% of 101 patients with venous ulcers in the city of Natal, in the Brazilian state of Rio Grande do Norte, and in 21.4% of 70 patients in the city of Évora, in Portugal 4 . Only 8.2% out of 122 inpatients with pressure injuries in Aracaju had a story of smoking 21 . Smoking is related to worse healing outcomes, besides contributing to the pathogenesis of some lesions, such as arterial ulcers 11,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation